Pemberian ASI Eksklusif dan Riwayat Imunisasi Sebagai Faktor Risiko Kejadian Pneumonia di Puskesmas Bangsal - Saputra, Mukhammad Himawan; Syalfina, Agustin Dwi; Fitriyah, Kharismatul; Yuniarti, Asih Media (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Pneumonia remains a leading cause of morbidity and mortality in children under five worldwide, including in Indonesia, with risk factors such as non-exclusive breastfeeding and incomplete immunization status. This study aimed to analyze the relationship between exclusive breastfeeding and immunization history with the incidence of pneumonia among children under five in the Working Area of Bangsal Community Health Center, Mojokerto Regency. A case-control design was employed, with a sample of 128 children (64 cases and 64 controls) selected through simple random sampling. Data were collected from medical records and interviews, then analyzed using the Chi-Square test. The results showed that most respondents had incomplete immunization status (51.6%) and received exclusive breastfeeding (55.5%). Statistical analysis revealed that complete immunization status was associated with a reduced risk of pneumonia (OR = 0.468; p = 0.034), as was exclusive breastfeeding (OR = 0.434; p = 0.021). The study concludes that complete immunization and exclusive breastfeeding serve as protective factors against pneumonia in children under five. Therefore, strengthening promotive and preventive programs, such as health education, catch-up immunization, and increasing exclusive breastfeeding coverage, is essential to reduce pneumonia incidence